2016
DOI: 10.1016/j.sjbs.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plant growth promoting bacterium, Enterobacter cloacae MSR1, isolated from roots of non-nodulating Medicago sativa

Abstract: The aim of the present study was to characterize the endophytic bacterial strain designated MSR1 that was isolated from inside the non-nodulating roots of Medicago sativa after surface-sterilization. MSR1 was identified as Enterobacter cloacae using both 16S rDNA gene sequence analysis and API20E biochemical identification system (Biomerieux, France). Furthermore, this bacterium was characterized using API50CH kit (Biomerieux, France) and tested for antibacterial activities against some food borne pathogens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
81
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 38 publications
3
81
0
6
Order By: Relevance
“…Enterobacteriaceae and Pseudomonadaceae are capable of secreting secondary metabolites or produce enzymes that enhance drought tolerance. For instance, volatile organic compounds such as acetoin and butanediol elicits stomatal closure, helping the plant prevent water loss from transpiration (Cho et al, 2008) and improving drought tolerance (Saha and Bothast, 1999;Celińska and Grajek, 2009;Ji et al, 2011;Khalifa et al, 2016). In addition, Pseudomonas, Klebsiella, Erwinia, Serratia and Pantoea species are known to be ACC deaminase-producing bacteria and therefore able to regulate plant ethylene levels inducing tolerance to drought stress (Li et al, 2015;Saikia et al, 2018;Danish and Zafar-ul-Hye, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae and Pseudomonadaceae are capable of secreting secondary metabolites or produce enzymes that enhance drought tolerance. For instance, volatile organic compounds such as acetoin and butanediol elicits stomatal closure, helping the plant prevent water loss from transpiration (Cho et al, 2008) and improving drought tolerance (Saha and Bothast, 1999;Celińska and Grajek, 2009;Ji et al, 2011;Khalifa et al, 2016). In addition, Pseudomonas, Klebsiella, Erwinia, Serratia and Pantoea species are known to be ACC deaminase-producing bacteria and therefore able to regulate plant ethylene levels inducing tolerance to drought stress (Li et al, 2015;Saikia et al, 2018;Danish and Zafar-ul-Hye, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This isolate was found to secrete N-butanoyl homoserine lactone (C4-HSL) and N-hexanoyl homoserine lactone (C6-HSL) (Lau, Sulaiman, Chen, Yin, & Chan, 2013;Lau, Yin, & Chan, 2014). Previous studies have shown that E. asburiae strains have been isolated from water, soil, food, and human sources, that is, blood culture, wounds, and exudates as well as from respiratory sources (Brenner, McWhorter, Kai, Steigerwalt, & Farmer, 1986; Castellanos-Arévalo, Castellanos-Arévalo, Camarena-Pozos, Colli-Mull, & Maldonado-Vega, 2015; Khalifa, Alsyeeh, Almalki, & Saleh, 2015;Shin et al, 2007). Although its exact clinical value is yet to be discovered and very little is known about its pathogenicity and virulence, these findings suggested the clinical significance of E. asburiae.…”
mentioning
confidence: 99%
“…Of Enterobacter spp., Enterobacter radicincitans in cereals (Witzel et al, 2012), Enterobacter sp. SP1 in sugar cane (Zhu et al, 2012) and Enterobacter cloacae MSR1 in alfalfa (Khalifa et al, 2016) have shown an ability to increase production in plants. The production of plant hormones by the Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%